2014
DOI: 10.2147/ndt.s71056
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic seizure therapy in an adolescent with refractory bipolar depression: a case report

Abstract: Magnetic seizure therapy (MST) has shown efficacy in adult patients with treatment-resistant depression with limited impairment in memory. To date, the use of MST in adolescent depression has not been reported. Here we describe the first successful use of MST in the treatment of an adolescent patient with refractory bipolar depression. This patient received MST in an ongoing open-label study for treatment-resistant major depression. Treatments employed a twin-coil MST apparatus, with the center of each coil pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…A case study evaluated MST in an adolescent with refractory bipolar disorder [24]. The patient remitted after 18 MST treatments that were followed by nine maintenance MST treatments over six months.…”
Section: Clinical Outcomementioning
confidence: 99%
“…A case study evaluated MST in an adolescent with refractory bipolar disorder [24]. The patient remitted after 18 MST treatments that were followed by nine maintenance MST treatments over six months.…”
Section: Clinical Outcomementioning
confidence: 99%
“…There also have been concerns about potential rTMS treatmentemergent mania/hypomania in the absence of adequate mood stabilizer treatment, suggesting that rTMS monotherapy (or in combination with an antidepressant) should be avoided in BD (Rachid, 2017). Magnetic seizure therapy has also been of interest, but has only case report-level evidence (Noda et al, 2014).…”
Section: Integration Of Pharmacotherapy With Nonpharmacological Appro...mentioning
confidence: 99%
“…75 There is a single case report in which the investigators reported full remission of depressive symptoms in an 18-year-old boy with refractory depression in the context of bipolar II disorder following 18 sessions of 100 Hz MST. 76…”
Section: Frontiers and Emerging Technologiesmentioning
confidence: 99%